Constrained vs Unconstrained Labor Supply: The Economics of Dual Job Holding - Chung Choe; Ronald L. Oaxaca; Francesco Renna (Global Labor Organization (GLO), 2017)
This paper develops a unified model of dual and unitary job holding based on a Stone-Geary utility function. The model incorporates both constrained and unconstrained labor supply. Panel data methods are adapted to accommodate unobserved heterogeneity and multinomial selection into 6 mutually exclusive labor supply regimes. We estimate the wage and income elasticities arising from selection and unobserved heterogeneity as well as from the Stone-Geary Slutsky equations. The labor supply model is estimated with data from the British Household Panel Survey 1991- 2008. Among dual job holders, our study finds that the Stone-Geary income and wage elasticities are much larger for labor supply to the second job compared with the main job. When the effects of selection and unobserved heterogeneity are taken account of, the magnitudes of these elasticities on the second job tend to be significantly reduced.
Keywords: J01; J22; J49; 330; dual job; labor supply; Stone-Geary; hours constraint